On the Economic Theory of Socialism: Part One - Lange, Oskar (Review of Economic Studies, 1936)
Journal Article On the Economic Theory of Socialism Get access Oskar Lange Oskar Lange Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 4, Issue 1, October 1936, Pages 53–71, https://doi.org/10.2307/2967660 Published: 01 October 1936